2019
DOI: 10.2478/mjss-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Internal Return Migration in Rural of Vietnam: Reasons and Consequences

Abstract: Many researchers have tried to explain the motivation behind out and return migration. However, few bodies of literature focus on selection of destinations of out migration, motives to return according to marriage status of migrants before the return and gender perspective of employments on the return. By surveying 68 returnees and applying participatory rural appraisal, this study shows that the personal and household characteristics of returnees before the migration create an effect on destination selections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The typology of return migration shown in the present work refers to the movement of workers and relatives from the more developed countries or regions to regions that provide labor in rural areas [60]. It is concluded that return migration presents several opportunities in terms of sustainable development, since the impact on consumption can be linked to the impact on production [9,[64][65][66][67][68][69][70][71][72][73][74][75][76][77]. Thus, emigrants are also people who return to live and work and cannot be considered exclusively in terms of the savings and consumption models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The typology of return migration shown in the present work refers to the movement of workers and relatives from the more developed countries or regions to regions that provide labor in rural areas [60]. It is concluded that return migration presents several opportunities in terms of sustainable development, since the impact on consumption can be linked to the impact on production [9,[64][65][66][67][68][69][70][71][72][73][74][75][76][77]. Thus, emigrants are also people who return to live and work and cannot be considered exclusively in terms of the savings and consumption models.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the rural-urban migration in the cities of Southern Europe also revealed that emigrants maintain strong ties to their land of origin, to which they return on vacation and, if the distance is not too far, on weekends [25]. Therefore, the emigration return movement, except in its initial phase (the departure), presents several opportunities, in terms of local development, since migrants preferentially return to their starting regions, which are the most in need of employment and income opportunities [9,[64][65][66][67][68][69][70][71][72][73][74][75][76][77]. However, in the countries of Southern Europe and the Mediterranean, there has been no impact of the return of emigrants on the development of their places of origin.…”
Section: Return Migration and Sustainable Development In Southern Europementioning
confidence: 99%
“…Thus, the emigration-return movement, except in its initial phase (the departure), has several potentialities in terms of rural development, since emigrants preferably head to the regions of departure, which are the most deprived [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. However, in the countries of Southern Europe and the Mediterranean, there has been no impact of the return of emigrants on the development of their places of origin.…”
Section: Return Migration Tourism and Sustainable Development And Lan...mentioning
confidence: 99%